Distraction osteogenesis in the craniomaxillofacial region. Part 1: history, principles, indications, types and protocol - Chi Adam, Khairul Bariah; Mahdah, S; Azmi, MN; Kadir, K; Nabil, S; Hariri, Firdaus (The Malaysian Association of Oral and Maxillofacial Surgeons, 2014)
Abstract: Distraction osteogenesis offers superior skeletal advancement compared to conventional osteotomy. As the surgical outcomes can be technically-dependent, it is important to understand the principle, indications, assessment and preparation prior to its application. This review is the first part of two articles which will provide clinicians updates on the history, principles, clinical indications, types of devices and protocol for distraction osteogenesis in the craniomaxillofacial region. Important issues in these essential aspects of distraction osteogenesis are comprehensively discussed based on clinical cases and supported by literature. Understanding the principles of distraction osteogenesis is mandatory to ensure optimum surgical outcome. The technique offers many advantages to the field of craniomaxillofacial surgery and can be considered as an alternative bone augmentation and lengthening technique as it produces stable and reliable outcomes.